Optimasi Portofolio Berdasarkan Model Mean-Variance dengan menggunakan Lagrange Multiplier pada saham IDX30 - Abdallah, Muhammad Naif; Febrianti, Werry; Mardianto, Lutfi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2024)
This study aims to optimize the portofolio of stocks included in the IDX30 index using the Mean-Variance model developed by Markowitz. The Lagrange Multiplier method is used in this study to determine the optimal fund allocation by minimizing risk and optimizing expected return. The data used is the daily closing price of stocks from 15 companies listed in the IDX30 index over the last five years (2019-2024). The results show that the Mean-Variance and Lagrange Multiplier methods are effective in identifying the optimal portofolio that can minimize investment risk while maximizing returns